Penerapan Model Pembelajaran Kepala Bernomor Struktur Untuk Meningkatkan Tanggung Jawab Siswa Pada Muatan Pembelajaran PPKn di Kelas V SD Babussalam - Nur Asiah (Amal Insani Foundation, 2024)
This study aimed to investigate students' increased responsibility for the content of civics education instruction in Grade 5 of Babussalam Elementary School, Pekanbaru Province. The reason for this study was students' lack of responsibility for preparing for their studies in advance, making effective use of their time, completing individual assignments, and seriously participating in discussions. It was action research in the classroom. The subjects of this study were teachers and 17 fifth grade students from Babusalam Primary School Pekanbaru. The goal was to implement a